SURGICAL OUTCOMES OF TREATMENT FOR BENIGN COLONIC PERFORATION AT CHO RAY HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Background: Benign colonic perforation is a severe surgical emergency that may cause peritonitis, sepsis, and organ failure. This study aimed to describe clinical and paraclinical characteristics, surgical management, and early postoperative outcomes at Cho Ray Hospital.Methods: A retrospective descriptive case series was conducted on 175 patients with benign colonic perforation who underwent emergency surgery between January and December 2025. Data were extracted from medical records, including patient characteristics, etiology and site of perforation, surgical approach, operative procedure, and early postoperative outcomes.Results: The mean age was 63.8 years (range, 16–92), and 61.1% were male. The mean duration of abdominal pain before admission was 2.34 days; 29 patients (16.6%) had hemodynamic shock on admission according to emergency/preoperative resuscitation records. Diverticular perforation was the most common etiology (79.4%), followed by foreign body perforation (12.0%) and undetermined causes (8.6%). The sigmoid colon was the most frequent site (56.0%). Open surgery accounted for 80.0%, and stoma-related procedures were used in most cases. Common complications included acute kidney injury (24.6%), pneumonia (18.9%), and multiorgan failure (13.7%). Postoperative mortality occurred in 15 cases (8.6%).Conclusions: Benign colonic perforation in this case series mainly affected older patients with comorbidities and was associated with considerable morbidity and mortality. These findings emphasize early diagnosis, active resuscitation, and individualized surgical decision-making according to the patient’s physiologic status.
Keywords: colonic perforation; peritonitis; stoma; emergency surgery.